The Impact of Comorbid Clinical Depression on The Health-Related Quality of Life of Adults on Highly Active Antiretroviral Therapy in Maiduguri, Northeastern Nigeria - Wakawa, Ibrahim Abdu (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Globally, depression compromises the quality of life (QOL) of people suffering from it. We assessed the impact of comorbid depression on the health-related quality of life (HRQOL) of adults on highly active antiretroviral therapy (HAART) in northeastern Nigeria in this study. MATERIALS AND METHODS: Three hundred and three adults on HAART were recruited for this study from the ART clinic of the University of Maiduguri Teaching Hospital in northeastern Nigeria. The depressive disorder module of the Composite international diagnostic interview (CIDI version 3.0) and the WHO quality of life instrument (WHOQOL-BREF) were used for the evaluation of depression and quality of life respectively. RESULTS: The prevalence of depression in this study was 19.8%. The depressed respondents rated their HRQOL poorer than their nondepressed counterparts on the physical, psychological, social relationships and environmental domains as well as the global outcome, as shown by these statistically significant findings (T = 9.739, P = <0.001), (T = 8.972, P = <0.001), (T = 6.533, P = <0.001), (T = 8.913, P = <0.001), and (T = 10.018, P = <0.001), respectively. Female gender, CD4 counts <200/mm(3) and diagnosis of depression were significant predictors poor QOL. CONCLUSION: Depression has a negative impact on the QOL of the respondents. We therefore recommend incorporation of the routine screening of this important psychiatric comorbidity into the care of this vulnerable group in order to optimize patient care.